Ảnh hưởng của sự tỉnh giác trong công việc đến các hành vi tự nguyện và kết quả làm việc của nhân viên - Nguyễn Thị Nguyệt, Quế (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
Extra-role behaviors and employee mindfulness have become increasingly important for the success of service organizations. This study aims to develop a theoretical framework and research hypotheses that explain the relationships between mindfulness and extra-role behaviors in enhancing employee performance. The survey results of frontline service employees of a large commercial bank in Vietnam confirm that mindfulness has a positive impact on both organizational-oriented citizenship behavior and customer-oriented citizenship behavior. Moreover, these extra-role behaviors, do not only have positive impacts on employee performance but also mediate the effect of mindfulness on employee performance. Our study provides some practical implications for service firms in Vietnam generally and banking organizations particularly in enhancing employee mindfulness and extra-role behaviors, thereby contributing to improve their job performance.